Pendidikan Anti Kekerasan Pada Anak Di Lingkungan Sekolah SMP YLPI Pekanbaru - Lidia Febrianti; Erika Desvianti; Puti Mayang Seruni; Zahra Nurmania (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Violence can occur in children at school, including physical, psychological and sexual violence. The same problem was also encountered at SMP YLPI Pekanbaru. The teachers feel that the civic education and moral education lessons provided are not capable of forming students' characteristics so that they avoid acts of violence, whether as perpetrators or victims. Based on discussions with the principal of SMP YLPI Pekanbaru, the problem found was that several students committed acts of violence that led to conflict, both verbally and physically. The solution offered is an anti-violence program in schools aimed at teachers and students. “The aim of this activity is to make YLPI Pekanbaru Middle School a school that is safe and free from violence against children.” The method for this program consists of material creation, counseling and evaluation stages. “The results of this activity are in the form of increased insight and knowledge of students and teachers regarding violent behavior in schools and how to prevent and overcome it.”